Digital economy and the law: introduction to this Special Issue. (1st December 2018) - ,; ,; ,
Abstract : This article introduces the special issue of Work Organisation, Labour & Globalisation on the digital economy and the law. After summarising the literature and setting out some of the key issues raised by digitalisation in general and online platforms in particular for labour rights, it introduces the contents of the issue in detail, positioning them in relation to these larger debates.